PENGEMBANGAN FILM ANIMASI 3D BERBASIS BUDAYA JAMBI TERINTEGRASI PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN MINAT BELAJAR SISWA - Novferma; Febbry Romundza; Asih Nur Ismiatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop and examine the feasibility and effectiveness of FILAD (3D Animated Film) based on Jambi local culture integrated with the Pancasila Student Profile in improving students’ literacy skills and learning interest at SMPN 7 Muaro Jambi. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate) involving 32 eighth-grade students and three expert validators. Research instruments included validation sheets, a literacy test, a learning interest questionnaire, and observation sheets. Data were analyzed using Aiken’s V, Cronbach’s Alpha, N-Gain, and paired sample t-test at a significance level of 0.05. The results indicated that FILAD was categorized as highly valid (mean score = 4.45; Aiken’s V = 0.86) and highly practical (88.5%). Empirically, students’ literacy skills significantly improved, with the mean score increasing from 58.20 to 82.40 and an N-Gain of 0.62 (moderate–high category). Students’ learning interest also increased significantly, as reflected by the rise in the high-interest category from 18% to 68% (p < 0.05). These findings demonstrate that integrating 3D animation, local cultural context, and character education effectively enhances both cognitive and affective learning outcomes while supporting the implementation of the Merdeka Curriculum within the framework of digital educational transformation.